(untitled) (مجلة جامعة سرت للعلوم الانسانية, 2023)
The prophetic praise poems are among the purposes of Arabic poetry that came into existence after the Muhammadan mission, and they are poems that glorify the birth of the Messenger - may God bless him and grant him peace - and his morals, his jihad, his miracles, his conquests, and his impact on spreading Islam and the pure Sunnah, all because of the religious passion flowing among Muslim poets Proverbs, Hassan bin Thabit, Kaab bin Zuhair, Al-Busiri, and Ahmed Shawky. The study aims to analyze the poem "Miss Narek" in praise of the Messenger, may God bless him and grant him peace, by the Syrian poet Anas al-Dughaim, and to identify the creative creation of the writer by using the method of stylistic analysis to search for the aesthetics of the literary work by diving into its deep structure to highlight the aesthetics and components of uniqueness and creativity in the literary effect. Through the levels of stylistic research represented in the phonetic level and the semantic level, the study concluded after entering into the deep structure of the text in revealing the sources and features of the literary work based on the fact that the literary effect consists of particles that are integrated and synergistic with each other to complete the integrated artistic image of the literary work. Through the analysis structural and artistic features existing in the literary text through phonetic and semantic analysis of the literary text.